Draft Annual Plan 1988-89 Vol. I Sectoral Profile Uttar Pradesh - Planning Commission (Planning Commission, 1987)
The problem of drought was encountered in the current year 1987-88 also. This year the drought is far more severe than what the State has faced during the century. Acute scarcity of rainfall has done considerable damage to Kharif crops. The standing Kharif crop was also adversely affected due to high temperature.
Government of Uttar Pradesh, Planning Department